Simulation of gas flow around the scoop in a two-dimensional (r-θ) centrifugal rotor using the direct Monte Carlo method - V. Ghazanfari; A.A. Ghorbanpour Khamseh; M.M Shademan; J. Safdari; M.H Askari (مجله علوم و فنون هسته‌ای, 2023)
One of the driving factors for creating axial flow inside the gas centrifuge rotor to increase the separation performance is the scoop. Due to the exposure of the scoop to the high Mach gas flow, the flow will be shocked, and strong gradients will occur in the flow.  In this research, the gas flow around the scoop in a two-dimensional state (r-θ) is simulated by the Direct Simulation Monte Carlo method (DSMC) using the dsmcFoam solver at different distances of the scoop from the rotor wall. The results show that increasing the distance of the scoop from the rotor wall and decreasing the contact angle of the gas flow with the scoop reduces the maximum temperature and drag force. For instance, increasing the distance of the scoop from the wall by 31% (from 8 to 10.5 mm) in 3800 Pa wall pressure and 85° contact angle, causing a maximum temperature decrease of 1.3% (from 596 to 588 K) and also the drag force is reduced by 49.4% (2412 to 1221 dyn). Furthermore, reducing the angle of the gas flow with the scoop by 11.8% (from 85 ° to 75 °) in 3800 Pa wall pressure and at the distance of the scoop from the wall equal to 10.5 mm causes a maximum temperature decrease of 6.8% (from 588 To 548 K) and the drag force is reduced by 50.3% (1552 to 771 dyn).